Analisis Rasio Keuangan Untuk Menilai Kinerja Keuangan Perusahaan Periklanan, Percetakan, Dan Media Yang Terdaftar Di Bursa Efek Indonesia Periode 2017-2021 - Silvia Indrarini; Galuh Budi Astuti; Aprilia Resida Cici Luhsari (Akubis : Jurnal Akuntansi dan Bisnis, 2024)
This research aims to analyze financial ratios to assess the financial performance of companies in Advertising, Printing and Media Companies Listed on the Indonesian Stock Exchange for the 2017-2021 Period. This type of research is a case study using secondary data. The population was 20 companies, sampling using the purposive sampling method selected 4 companies as samples. Library study data collection methods and documentation data collection techniques, as well as quantitative descriptive data analysis techniques. The results of the financial ratio analysis of the company that has the best Current Ratio value is PT Jasuindo Tiga Perkasa Tbk, the best Cash Ratio value is PT Surya Citra Media Tbk, the best Debt to Asset Ratio value is PT Surya Citra Media Tbk, the best Debt to Equity Ratio value PT Surya Citra Media Tbk, the best Return On Asset value PT Surya Citra Media Tbk, the best Net Profit Margin value PT Surya Citra Media Tbk, the best Receivable Turnover value PT Link Net Tbk, the best Total Asset Turnover value PT Jasuindo Tiga Perkasa Tbk, the best Price Earning Ratio value for PT Link Net Tbk, and the best Price To Book Value for PT Link Net Tbk.